'Uncomradely and Un-communist': Breakdown in the Communist Anglosphere? The Communist Party of Great Britain and Communist Party of Australia Debate, 1947–1948. Issue 1 (1st April 2023) - Billam, Gregory
Abstract : The communist parties of Britain's empire were notably excluded from the newly established Cominform in September 1947. In their absence, previous hierarchical relationships became less clear, as the fiery exchange between the CPA (Australia) and CPGB (Great Britain) in 1947 and 1948 illustrated the breakdown in 'civil comradely debate' to be expected between two fraternal CPs. The article will delve into the content of the debate itself – which until now has been dealt with only in passing – illuminating the differences in ideological direction: on anti-imperialism, on 'the transition to socialism', and ultimately on the raison d'être of a post-war Communist Party. The article argues that the exchange signalled the shifting relationships and ideological realignments within the international communist movement, under the increasing weight of the Cold War and decolonization. It is also argued that the accusations of Marxist impurity and sectarianism, such as the 'charges' of Browderism and Titoism, demonstrate the policing of international communist debate, and the embryonic 'national roads to socialism' policy.